Harmonization of Protocols for Multi-Species Organoid Platforms to Study the Intestinal Biology of Toxoplasma gondii and Other Protozoan Infections - Holthaus, David; Delgado-Betancourt, Estefanía; Aebischer, Toni; Seeber, Frank; Klotz, Christian (Frontiers in Cellular and Infection Microbiology, 2021)
The small intestinal epithelium is the primary route of infection for many protozoan parasites. Understanding the mechanisms of infection, however, has been hindered due to the lack of appropriate models that recapitulate the complexity of the intestinal epithelium. Here, we describe an in vitro platform using stem cell-derived intestinal organoids established for four species that are important hosts of Apicomplexa and other protozoa in a zoonotic context: human, mouse, pig and chicken. The focus was set to create organoid-derived monolayers (ODMs) using the transwell system amenable for infection studies, and we provide straightforward guidelines for their generation and differentiation from organ-derived intestinal crypts. To this end, we reduced medium variations to an absolute minimum, allowing generation and differentiation of three-dimensional organoids for all four species and the subsequent generation of ODMs. Quantitative RT-PCR, immunolabeling with antibodies against marker proteins as well as transepithelial-electrical resistance (TEER) measurements were used to characterize ODM’s integrity and functional state. These experiments show an overall uniform generation of monolayers suitable for Toxoplasma gondii infection, although robustness in terms of generation of stable TEER levels and cell differentiation status varies from species to species. Murine duodenal ODMs were then infected with T. gondii and/or Giardia duodenalis, two parasites that temporarily co-inhabit the intestinal niche but have not been studied previously in cellular co-infection models. T. gondii alone did not alter TEER values, integrity and transcriptional abundance of tight junction components. In contrast, in G. duodenalis-infected ODMs all these parameters were altered and T. gondii had no apparent influence on the G. duodenalis-triggered phenotype. In conclusion, we provide robust protocols for the generation, differentiation and characterization of intestinal organoids and ODMs from four species. We show its applications for comparative studies on parasite-host interactions during the early phase of a T. gondii infection but also its use for co-infections with other relevant intestinal protozoans.